An Anthropological Account of a Visit to the Museum Istiqlal - Jonathan Zilberg (Lajnah Pentashihan Mushaf Al-Qur'an, 2010)
The purpose of this article is fourfold. Firstly, it expands upon the previous anthropological discussion of the Museum Istiqlal in Indonesia. Secondly, it reflects on the national importance of the intended role of the Museum Istiqlal in promoting this identity. Thirdly, this article considers problematic aspects of the collection itself, the state of the museum and above all—the unfulfilled potential the Museum Istiqlal offers for Islamic education in Indonesia. Fourthly, it provides a relatively extensive bibliography so as to introduces some of the substantial academic literature which is relevant to the collection and thus of potential use to scholars and museum specialists potentially interested in this under-utilized museum.